Clinical Characteristics of Choroidal Metastases - Bożena Romanowska-Dixon; Karolina Gerba-Górecka; Agnieszka Nowak; Joanna Kowal; Magdalena Dębicka-Kumela; Dagmara Nowak (Okulistyka)
The most common intraocular tumors in adults are metastases from primary tumors: breast cancer, lung cancer, and other organ neoplasms. They are most typically located in the choroid, in the posterior pole of the eye. This article outlines the characteristic clinical features along with ultrasound and optical coherence tomography findings that aid in differential diagnosis. It also illustrates the growth pattern of metastatic nodules from their formation to their eventual fusion into a diffuse tumor conglomerate with an irregularly shaped surface and internal structure